Effects of Methylphenidate and Atomoxetine on Cortical Inhibition in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The effects of methylphenidate (MPH), a psychostimulant, and atomoxetine (ATX), a selective norepinephrine reuptake inhibitor, on short interval-cortical inhibition (SICI) were measured in motor cortex with transcranial magnetic stimulation, in a study at Cincinnati Children's Medical Center, OH, and other centers.